Mencius: Contexts and interpretations - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2009)
Mencius: Contexts and Interpretations. Edited by Alan K. L. Chan. (Honolulu: University of Hawaii Press, 2002. 328 pp.) This is a collection of new essays by various authors. It includes a brief but good introduction to Mencius, the Mencius, and the essays in this collection. There is a general index and an index locorum.